Synthesis, Antiviral, and Antimicrobial Evaluation of Benzyl Protected Diversified C-nucleosides - Bari, Ahmed; Ali, Syed S.; Alanazi, Amer M.; Mashwani, Muhammad A.; Al-Obaid, Abdulrahman M. (Frontiers in Chemistry, 2018)
Formyl glycals are the versatile synthetic intermediates and can serves as precursor for the synthesis of various C and N-nucleosides. Due to the presence of electron donating and electron withdrawing character on formyl sugars which makes the molecule more susceptible to nucleophilic attack we propose the synthesis of diversified C-nucleosides (3-14) by reaction with N,N dinucleophiles utilizing same strategy. These nucleosides were than tested against viral, bacterial and fungal strains.